2004
DOI: 10.2165/00063030-200418030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Reproducible Procedure for Plasmid DNA Encapsulation by Red Blood Cell Ghosts

Abstract: Transfection studies have demonstrated that pGL3 DNA carrying the luciferase gene is successfully transferred from RBC ghosts to recipient HeLa cells in culture under mild fusion conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This is in accordance with the findings of Chittchang et al45 who found that the random coil is the native secondary structure of polylysine. Although hydrophobicity of poly- l -lysine significantly increases in the order; random coil < α-helix < β-sheet conformers,46 we know from our previous experience that complexes of poly- l -lysine and poly- l -glutamic acid have a degree of hydrophobicity, as we have shown that conjugates of polylysine electrostatically bind to DNA and make good cell-transfecting agents 47. Moreover, poly- l -lysine adopts a β-sheet conformation from the random coil during interaction with phospholipids 48.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the findings of Chittchang et al45 who found that the random coil is the native secondary structure of polylysine. Although hydrophobicity of poly- l -lysine significantly increases in the order; random coil < α-helix < β-sheet conformers,46 we know from our previous experience that complexes of poly- l -lysine and poly- l -glutamic acid have a degree of hydrophobicity, as we have shown that conjugates of polylysine electrostatically bind to DNA and make good cell-transfecting agents 47. Moreover, poly- l -lysine adopts a β-sheet conformation from the random coil during interaction with phospholipids 48.…”
Section: Discussionmentioning
confidence: 99%
“…McNeil et al (36) and others (37,38) describe "scrape loading" as a means to transfer larger molecules across the cell membrane, but "scrape loading" of adherent A-NK cells with AP leads to heterogenous uptake and a significant loss of cells. Other techniques, such as red blood cell ghost fusion (39)(40)(41)(42) and electroporation (43)(44)(45)(46)(47) as a means to get enzymes across the cell membrane, also resulted in heterogeneous labeling and considerable cell loss when applied to the A-NK cells and were therefore not further pursued. In contrast, the ability of PTD to transduce A-NK cells with various molecules, such as FITC, AP, and beta-gal, was very impressive.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, multiple variations of this have been developed, like Hb precipitation with PEG [ 111 ], pre-incubation with a hypotonic drug solution and then hypertonic resealing [ 112 ], and gradual drug loading [ 109 ]. In the only recent paper on the efficient loading of RBC ghosts with plasmidic DNA [ 100 ], Larson et al pre-swelled them in hypotonic phosphate buffer, incubated with plasmidic DNA, than concluded with resealing, adding a hypertonic solution of sodium chloride. The hypotonic pre-swelling approach was commonly used in the 1980s to load RBC ghosts with both RNA and DNA.…”
Section: Erythrocyte-based Ddssmentioning
confidence: 99%